CLINICOPATHOLOGICAL FEATURES OF ALK POSITIVE AND ALK NEGATIVE ANAPLASTIC LARGE CELL LYMPHOMA: A SINGLE INSTITUTE (Journal of Medical & Health Sciences Review, 2025)
Background: Anaplastic large cell lymphoma (ALCL) is a rare and aggressive T-cell lymphoma, with limited information on its clinical and pathological characteristics in the Pakistani population.Objective: The study aims to examine clinical, pathological, and prognostic factors in both ALK-positive and ALK-negative ALCL cases.Materials and Methods: A total of 49 diagnosed cases from Shaukat Khanum Memorial Cancer Hospital over ten years (2013-2023) were analyzed for various clinical and prognostic factors.Results: Out of 49 cases, 22 (44.9%) were ALK-positive and 27 (55.1%) were ALK-negative. The median age for ALK-positive patients was 12.5 years, while ALK-negative patients had a median age of 28 years. Notably, ALK-negative patients were younger than reported in other studies, potentially due to geographic differences.Common symptoms included lymphadenopathy, observed in 12 cases of each subtype, with advanced clinical stage 4 being prevalent. Histological patterns were similar across subtypes.Outcome Measures: The median overall survival was 12 months for ALK-positive and 15 months for ALK-negative cases, with progression-free survival of 34 months for ALK-positive and 12 months for ALK-negative. There was no significant survival difference based on ALK status, although ALK-positive cases had better progression-free survival.Conclusion: ALCL in Pakistan often presents at advanced stages and younger ages than global data suggests. ALK expression did not impact overall survival but correlated with longer progression-free survival in ALK-positive cases. The findings highlight the need for improved detection and treatment strategies in the region.